A method for the long-term cultivation of mammalian cells in the absence of oxygen: Characterization of cell replication, hypoxia-inducible factor expression and reactive oxygen species production. (February 2018) - Plotkin, Balbina J.; Davis, James W.; Strizzi, Luigi; Lee, Peter; Christoffersen-Cebi, Jayme; Kacmar, Joan; Rivero, Orlando J.; Elsayed, Norhan; Zanghi, Nicholas; Ito, Brent; Sigar, Ira M.
Graphical abstract: Highlights: A method for long term sustainable anoxic culture of mammalian cells is described. Cells under anaerobic cultivation undergo morphologic differentiation. Anaerobically cultured cells replicate and release reactive oxygen intermediates. HIF1 mRNA expression and HIF protein levels cycled. Abstract: The center of tumors, stem cell niches and mucosal surfaces all represent areas of the body that are reported to be anoxic. However, long-term study of anoxic cell physiology is hindered by the lack of a sustainable method permitting cell cultivation in the complete absence of oxygen. A novel methodology was developed that enabled anoxic cell cultivation (17d maximum time tested) and cell passage. In the absence of oxygen, cell morphology is significantly altered. All cells tested exhibited morphologic changes, i.e., a combination of tethered (monolayer-like) and runagate (suspension-like) morphologies. Both morphologies replicated (Vero and HeLa cells tested) and could be passaged anaerobically. In the absence of exogenous oxygen, anoxic cells produced reactive oxygen species (ROS). Anaerobic runagate HeLa and Vero cells increased ROS production from day 3 to day 10 by 2- and 3-fold, respectively. In contrast, anoxic tethered HeLa and Vero cells either showed no significant change in ROS production between days 3 and 10 or exhibited a 3-fold decrease in ROS, respectively. Detection of ROS was inversely related to detection of hypoxia-inducible factor-1α ( HIF1 ) mRNA and HIF-1 protein expression which cycled over a 10-day period. This methodology has broad applications for the study of tumor and stem cell physiology as well as gastrointestinal cell-microbiome interactions. In addition, sustainable anaerobic cell culture may lead to the identification of novel pathways and targets for chemotherapeutic drug development.